Development Of Basketball Physical Condition To Age Group 14 Years Old From Club Human (Hutama Manggala) In Malang City - Yudha Kusuma, Bagas; Ratna Wulan, Dwi; Brevas Toumahuw, Deniver; Az Zahra, Fadhilah; Widiawati, Prisca (Journal of Comprehensive Science, 2023)
The purpose of this study was to determine the formation of the physical condition of basketball at the Human Club (Hutama Manggala) Malang City. The research method used is descriptive quantitative. Data collection techniques in this study used tests and measurements. The form of the test in this study took several tests of pre-existing physical conditions through several series of tests. These tests and measurements are very important to measure an athlete's ability to know enough or not enough in training. Through the existing test results, it canbe concluded that many athletes really train very hard to get a satisfactory score